Indonesia's identity politics and populism: Disruption to national cohesion - Arifin, Firdaus; Tedjabuwana, Rosa; Wiyono, Subelo; Abdullah, Mohd. Kamarulnizam Bin (Universitas Negeri Yogyakarta, 2025)
The principle of unity in diversity in Indonesia is increasingly challenged by the rise of identity politics and populism. These dynamics emerge as a confluence of pragmatic political strategies and the mobilisation of sectarian groups, often leveraging religious and ethnic sentiments during election campaigns. While effective in garnering popular support, such tactics undermine national unity and social cohesion, serving as a shortcut to power at the cost of societal harmony. This issue is particularly pronounced in district head elections, where the politicisation of tribal, religious, racial, and inter-community identities has become pervasive. These elections, intended to reflect democratic principles, are frequently overshadowed by divisive identity-based politics. This paper examines how identity politics and populism significantly threaten social cohesion, especially during general elections. Employing a normative research methodology, it analyses legal norms and ethical theories to argue against the use of identity politics and populism at any level of political campaigns. The findings reveal that practical politics in Indonesia often relies on these divisive strategies for electoral success, exacerbating pre-existing societal tensions. The paper posits that identity politics can be overcome with reinterpreting it and referring to Pancasila as a principle to attain better policy.